Case Report: Cytoreductive nephrectomy and thrombectomy in metastatic renal cell carcinoma with venous tumor thrombus: a case using indocyanine green fluorescence-guided laparoscopy - Dong, Xiaoyong; Zhang, Jie; Pan, Yongjun; Xie, Tiejun; Wang, Jinhua (Frontiers in Oncology, 2025)
Background and ObjectiveIndocyanine green (ICG) is a widely utilized non-radiative fluorescent contrast agent that has progressively demonstrated unique advantages in urological endoscopic surgeries in recent years. Despite its potential advantages, to date, no reports have detailed the use of fluorescence laparoscopy in cytoreductive nephrectomy and thrombectomy(CNT) for metastatic renal cell carcinoma (mRCC) complicated by renal vein tumor thrombus. This paper presents a single-case clinical experience of CNT for mRCC with renal vein tumor thrombus, with procedures guided by ICG fluorescence-guided laparoscopy.MethodsWe retrospectively analyzed the clinical data of a patient diagnosed with mRCC complicated by renal vein tumor thrombus. The patient underwent CNT at Beibei Hospital, Chongqing Medical University on November 7, 2023.ResultsA 65-year-old male had a left renal tumor, systemic metastases, and left renal vein tumor thrombus shown by preoperative computed tomography(CT). Before surgery, he received seven cycles of anti PD-1 (Toripalimab) immunotherapy and 20 days of pazopanib (anti-vascular TKI), which was stopped due to liver impairment. After treatment, the left renal lesion shrank and some metastases vanished. As the patient was in good condition and willing to have surgery, CNT was done under ICG fluorescence-guided laparoscopy successfully. Post-operative pathology confirmed left kidney clear cell carcinoma with left renal vein tumor thrombus. No complications occurred, and the patient recovered and was discharged. Regular rechecks of 16 months showed no tumor progression.ConclusionICG fluorescence real-time imaging technology is characterized by real-time dynamics, convenience and safety. Performing CNT for mRCC with tumor thrombus in the renal vein under ICG fluorescence navigation laparoscopy is safe and feasible.